Dakwah Ekologis Khalifah: Telaah Al-Baqarah Ayat 30 dan Relevansinya terhadap Sustainability Management - Rusmiati, Imam Fatkhullah; Mahmud, Hamidullah (Institut Agama Islam Negeri Kerinci, 2025)
This article explores the ecological mandate in Surah Al-Baqarah verse 30, which positions humans as khalifah entrusted with the responsibility of preserving the earth, and examines its connection with contemporary sustainability management. The study employs a qualitative approach based on literature review, analyzing Qur’anic exegesis alongside recent academic journals on Islamic environmental ethics and sustainability management. The findings demonstrate that the concept of khalifah in Islam is strongly aligned with modern principles of sustainable development, particularly in terms of justice, balance, and intergenerational responsibility. Its practical implications are reflected in organizational governance, the development of the green economy, and religious-based education that fosters collective ecological awareness. The conceptual synthesis further highlights that maqasid al-shariah can be expanded as a normative foundation for environmental protection, thereby enriching sustainability management paradigms that are not only technical and economic but also spiritual and moral. Thus, Islam offers significant contributions to the global discourse on sustainability by integrating religious values into contemporary management practices.